Programmable Adaptive BVT for Future Optical Metro Networks Adopting SOA-Based Switching Nodes - Martín González, Laura; Van der Heide, Sjoerd; Xue, Xuwei; Van Weerdenburg, John; Calabretta, Nicola; Okonkwo, Chigo; Fàbrega, Josep M.; Svaluto Moreolo, Michela (Photonics, 2018)
Adaptive Sliceable-Bandwidth Variable Transceivers (S-BVTs) are key enablers for future optical networks. In particular, those based on Discrete MultiTone (DMT) modulation and Direct Detection (DD) can be considered a flexible solution suitable to address the cost efficiency requirement of optical metro networks. In this paper, we propose to use a cost-effective S-BVT option/implementation in optical metro networks adopting switching nodes based on Semiconductor Optical Amplifier (SOA) technology. Bit loading (BL) and power loading (PL) algorithms are applied to the Digital Signal Processing (DSP) modules, to maximize the performance and/or the capacity as well as enhance the flexibility and adaptability of the system. Our analysis considers switching nodes based on SOAs with and without filtering elements and fiber spans of 25 km. We present the results up to 100 km, with and without SOA-based nodes. Firstly, we analyze the adaptive BVT transmission using the Margin Adaptive (MA) BL/PL algorithm at a fixed bit rate of 28 Gb/s. The possibility of controlling the SOAs current is a key factor to face the transmission impairments due to the fiber and the filtering elements. We also analyze the system considering Rate Adaptive (RA) transmission at a fixed target Bit Error Rate (BER) of 3.8 × 10−3, showing that a maximum capacity above 34 Gb/s can be achieved for a single span of 25 km. Although the cascading of filtering elements still constitutes a limiting factor, we show that an improvement of the net bit rate performance can be obtained thanks to the combined use of BVT and SOA technology at the switching nodes, resulting in a promising approach for designing future optical metro networks.